Perception of the infant death and dying process by resident nurses in child health - Jefferson Wildes da Silva Moura; Eliane Maria Ribeiro de Vasconcelos; Celia Maria Ribeiro de Vasconcelos; Kaili da Silva Medeiros; Filipe Souza Lemos; Maria Gabrielle Moreira Santos Silva (Universidade de Pernambuco, 2022)
Objective: to analyze the perception of resident nurses in Child Health regarding the process of infant death and dying in Pediatrics. Method: qualitative study, developed with four resident nurses from a University Hospital in Recife, Pernambuco, Brazil. The sample was selected by non-probabilistic sampling of the intentional type. The interviews were processed in IRAMUTEQ software and analyzed using the Descending Hierarchical Classification. Results: the following categories were observed: 1) coping with infant death; 2) process of pediatric death and dying; 3) expression of feelings before infant death; 4) formation and resilience of the multidisciplinary team before the end of life; 5) residency experiences. Final considerations: despite being part of the vital cycle of living beings, death is seen as a tragic event, especially in childhood, awakening different feelings, mostly negative.